Pedaling out of poverty: social impact of a manual irrigation technology in South Asia - Shah, Tushaar; Alam, Muhammad Mehboob; Kumar, M. Dinesh; Nagar, R.K.; Singh, M. (International Water Management Institute, 2000)
An assessment of the social impact of treadle pump technology for manual irrigation in eastern India, the Nepal Terai, and Bangladesh, South Asia's so-called "poverty square." Treadle pump technology can be a powerful tool for poverty reduction in this region. It "self-selects" the poor, and puts to productive use the region's vast surplus family labor. It is claimed that the treadle pump could raise the annual net household income by US$100, on the average.